Does Repetitive Negative Thinking Influence Alcohol Use? A Systematic Review of the Literature - Devynck, Faustine; Rousseau, Amélie; Romo, Lucia (Frontiers in Psychology, 2019)
Over the past twenty years, researchers have used various methodologies to assess different forms of repetitive negative thinking (RNT) and their influence on alcohol consumption. Contrasting results between clinical and general populations were observed. To summarize the current literature on RNT and alcohol use, a systematic review was conducted according to the Preferred Reporting for Systematic Review and Meta-Analysis (PRISMA) guidelines (Moher et al. 2009). Among the twenty-seven included studies, the seven conducted among patients with alcohol use disorder (AUD) and the three focusing on other adult samples demonstrated a strong positive association between RNT and alcohol use or alcohol-related problems, regardless of the form of RNT. The results were more heterogeneous in the seventeen studies conducted among adolescents and students, leading the authors to conclude that the results varied as a function of the severity of alcohol use. The results of this study suggest to focus on RNT from a transdiagnostic perspective in AUD. This processual approach may improve AUD treatment and relapse prevention. Finally, some gaps in the literature must be addressed: (1) the gender differences in the link between RNT and alcohol use and (2) the specific influence of RNT on alcohol use among young adults.